Specialization and Sectorial Competitiveness of the Planning Territories of Sergipe in the collection of ICMS (Gestão & Regionalidade, 2023)
This paper analyzes the change that has taken place in the participation of different sectors in the planning territories of Sergipe through the ICMS collection in the 2016-2020 period. For that, the differential-structural method was used with the change proposed by Esteban-Marquillas (1972). The main results indicate that, despite the region of Grande Aracaju still being the main productive engine of the state, there was an expressive interiorization of some sectors, such as agriculture and commerce, which became specialized and competitive in several territories of the state's planning. Industry and services, in turn, despite still having a competitive advantage in most territories, have been losing their degree of specialization over the period.
Keywords: ICMS. Sergipe. Shift-Share.